An Investigation about the Influence of Bleaching on Shear Bond Strength of Orthodontic Brackets and on Enamel Colour. (22nd March 2012) - Immerz, Isabell; Proff, Peter; Roemer, Piero; Reicheneder, Claudia; Faltermeier, Andreas
Abstract : The aim of the study was to investigate the effect of bleaching on the colouration of tooth enamel and shear bond strength of orthodontic ceramic brackets based upon current whitening practice. The bleaching and bonding techniques were performed on extracted bovine teeth for the investigation of their colorimetric spectrum and the adhesive bond strength on surface enamel. One group was designated as the control group with no pre-treatment. Another group was treated with a 45% hydrogen peroxide solution prior to bonding. The difference in colour was expressed as the Euclidian distance Δ E . The resulting shear bond strength was analyzed and evaluated by scores of Adhesion Remnant Index. Statistical analysis was performed using the Kruskall-Wallis and post-hoc test. The colorimetric analysis revealed statistically significant differences between original and bleached as well as bleached and debonded teeth setting off a blue colour shift. Furthermore, statistically there was no significant difference noted in bonding strength between non-treated surfaces and those treated with peroxide. It can be concluded that peroxide pre-treatment does result in colour differences of teeth. Bonding and debonding procedures seem to have no statistically significant influence on the enamel colour using current materials.